GA Houses 188. - Futagawa, Yoshio; Hitomi, Saito (Tokyo : A.D.A. EDITA Tokyo Co., Ltd., 2023)
Johnston Marklee: Canal House ; Bernardes Arquitetura: Trianguo House & Bela Vista House ; Takamasa Yosizaka: Villa Coucou ; Jo Nagasaka: DOKUBO + EL AMIGO ; Ryue Nishizwawa + MISAWA: SATO HOUSE ; Gustavo Utrabo + Pedro Lass Duchenes: House + House ; Nobushiro Kitazawa: Ogawa House ; Satoshi Matsuko + Yuki Tamura: House on Sites ; Terra e Tuma Arquitetos: Jabuticabeiras House & Ubaira House
boek